Pencapaian tujuan pembangunan berkelanjutan kesetaraan gender di sektor pertanian Indonesia - Ikhwan, Rizghina; Raharjo, Agung Saras Sri; Arrozi, Ahmad Makki (Analisis Kebijakan Pertanian, 2025)
One of the critical discussions at the global and national levels that is relevant to the issue of gender equality is the role and involvement of women in the agrifood system, especially about women’s ownership of agricultural land. In reality, ownership or control over land rights in Indonesia is still dominated by men. This study aims to learn government policies and formulate recommendations to achieve the Sustainable Development Goals (SDGs) for gender equality in agriculture. The analytical method used in this study is a literature study supported by relevant data and information from various sources. The study results show that women’s access to control, ownership, utilization, and maintenance of natural resources, primarily agricultural land, is still low, meaning that the gender equality aspect in the TPB with indicators of the proportion of women population who have rights to agricultural land is still low. The lack of gender-disaggregated data in survey or census results supports this finding. It is recommended that the government increase its commitment to gender equality issues through various regulations, one of which is related to women’s rights to agricultural land. In addition, the government is advised to make gender-disaggregated data an essential and strategic part of development policies.